Adaptation of Venezuelan refugees in Colombia: the mediating roles of acculturation orientations in influencing acculturation adaptations (2023)
As of 2021, over 5.4 million Venezuelans have fled their home country in search of safety, food, medicine and access to essential services. This is the most substantial exodus in the recent history of Latin America. Colombia has received 2 million of these refugees, making it the nation host to the greatest number of Venezuelan refugees. The present research aims to examine the relations between the sociocultural and psychological factors that are associated with Psychological Adaptation of Venezuelan refugees living in Colombia. We also examined how these relations were mediated by the acculturation orientations. Among Venezuelan refugees, higher Psychological Strength, lower Perceived Discrimination, higher National Identity and higher Outgroup Social Support, were significantly associated with higher engagement with Colombian society and better Psychological Adaptation. Orientation to the host (Colombian) society mediated the association between (a) National Identity and Psychological Adaptation, (b) Outgroup Social Support and Psychological Adaptation and (c) Perceived Discrimination and Psychological Adaptation. The results may inform refugee receiving societies of some essential factors and positive strategies behind adaptation of refugees.